Respuesta :
Answer:
[tex]36^\circ, 108^\circ, 36^\circ[/tex]
Step-by-step explanation:
In [tex]\triangle ABC[/tex], sides AB = AC.
We know the property that angles opposite to equal sides in a triangle are equal.
Hence, [tex]\angle ABC = \angle ACB[/tex]
Let this angle be x.
So, [tex]\angle ABC = \angle ACB = x ...... (1)[/tex]
Similarly, in [tex]\triangle ABD[/tex]
Hence, [tex]\angle ABD = \angle BAD[/tex]
[tex]\angle ABD[/tex] and [tex]\angle ABC[/tex] are same.
By equation (1):
[tex]\angle ABD = \angle BAD = x ...... (2)[/tex]
Similarly, in [tex]\triangle ADC[/tex]:
[tex]\angle ADC = \angle DAC[/tex]
Let this angle be y.
[tex]\Rightarrow \angle ADC = \angle DAC = y ...... (3)[/tex]
We know that sum of all three angles in a triangle is equal to [tex]180 ^\circ[/tex].
In [tex]\triangle ADC[/tex], sum of all three angles:
[tex]x + y + y = 180^\circ\\\Rightarrow x + 2y = 180 ...... (4)[/tex]
In [tex]\triangle ABC[/tex], sum of all three angles:
[tex]x + (x+y) + x = 180\\\Rightarrow 3x + y = 180 ...... (5)[/tex]
Using elimination method to solve equation (4) and (5):
Multiplying equation (5) by 2 and subtracting (4) from it:
[tex]5x = 180\\\Rightarrow x = 36^\circ[/tex]
Putting value of x in (4):
[tex]36^\circ + 2y = 180\\\Rightarrow y = 72^\circ[/tex]
So, angles of [tex]\triangle ABC[/tex] are:
x, (x+y) and y
[tex]\Rightarrow 36^\circ, 108^\circ \text{ and } 36^\circ[/tex]